ANALYSIS OF MODELING AND DESIGN TECHNOLOGIES OF SYSTEMEDUCATIONAL FUNCTIONALS - Tamara Pushkarova; Oleksandr Hrytsenko; Mariya Koval-Mazyuta (Scientific Journal of Polonia University, 2025)
The work presented for discussion by the pedagogical community discusses the technological algorithm of modelling and design procedures, as well as their identical or different characteristics, organizational features and resulting capabilities. Practically performing a single research function in terms of predictive analysis of the behavioural trajectory of a given system functional, the modelling and design processes have somewhat different end products: a model and a project. Thus, it is reasonable to recognize that while the model provides an opportunity to study a real system functional on the basis of its simplified model copy, the project provides for the compilation of an existing algorithmized technology for studying a real system functional with sequential execution of a set of tasks. Considering the specific features of the application of modelling and design procedures in the education system, it makes sense to note that since this construct is classified as complex and multi-vector system organizations, the actual and full implementation of procedural modelling or design tasks in the field of educational activity looks like a difficult task, which will require a thorough study of the characteristic attributes and properties of an analogous object, the dynamics of its structural transformations and the influence on its activities of certain factors of endogenous or exogenous origin, the relationship and mutual influence of components and individual elements, the synergistic effect in the course of identifying the target capacity of such an object.